2017
DOI: 10.3389/fmicb.2017.00510
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Salmonella enterica Serovar Typhimurium in Shanghai, China

Abstract: We aimed to analyze the antimicrobial resistance phenotypes and to elucidate the molecular mechanisms underlying resistance to cephalosporins, ciprofloxacin, and azithromycin in Salmonella enterica serovar Typhimurium isolates identified from patients with diarrhea in Shanghai. The isolates showed high rates of resistance to traditional antimicrobials, and 20.6, 12.7, and 5.5% of them exhibited decreased susceptibility to cephalosporins, ciprofloxacin, and azithromycin, respectively. Notably, 473 (84.6%) isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
40
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 39 publications
11
40
2
1
Order By: Relevance
“…The study of the most frequent alleles obtained from the isolates of the different origins and the higher discriminatory index (DI), showed that ST6 was the loci with highest discriminatory index, and it may be of potential use for source attribution. Previous studies supported our results [9,36]. On the other hand, STTR10 and ST8 locus were absent in many strains (46.6% and 48.8%, respectively).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study of the most frequent alleles obtained from the isolates of the different origins and the higher discriminatory index (DI), showed that ST6 was the loci with highest discriminatory index, and it may be of potential use for source attribution. Previous studies supported our results [9,36]. On the other hand, STTR10 and ST8 locus were absent in many strains (46.6% and 48.8%, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…The most common resistance profile in human origin strains was AMP-TIC-TET-MIN-SXT (26%), and for poultry strains it was TET-MIN (38.8%) and AMP-TIC-TET-MIN (33.3%), suggesting that a possible gene transference of S. Typhimurium strains between these two sources might have happened. The S. Typhimurium exhibited high rates of resistance to traditional antibiotics such as ampicillin, nalidixic acid, tetracycline and sulfamethoxazole-trimethoprim; this is in accordance with the findings of other authors [35,36]. The detection of antimicrobial genes and a strict policy for the rational use of antibiotics for treating animals and humans is needed, if we do not want to have to limit the therapeutical choices for treating salmonellosis [5].…”
Section: Discussionsupporting
confidence: 81%
“…In Europe, the first case of failure of AZM treatment of Salmonella infection was reported [49]. Similarly, emergence of clinical AZM-resistant Salmonella isolates was recently reported in Asia [50, 51]; 15.24% of Salmonella isolates from chicken showed resistance to AZM (with an MIC ≥16 μg/mL) in another study [52]. However, reports of AZM resistance in Salmonella isolates from humans or animals in South Korea are rare.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many of the strains were multidrug resistant (MDR) with some even being resistant to more than seven antibiotics. Wang et al also showed that 84.6% of the Salmonella isolates from Shanghai, China, exhibited MDR and proved that resistance genes play an important role in MDR (Wang et al, ). Our findings indicate that it is necessary to continue monitoring the antimicrobial resistance of Salmonella isolates to help determine the appropriate antimicrobial therapy for patients infected with this pathogen.…”
Section: Discussionmentioning
confidence: 99%